The Meaning of ṿtsvʾ gdṿl in Daniel 10,1 - Kuryliak, Ihor (Scandinavian journal of the Old Testament, 2025)
The meaning of the phrase ṿtsvʾ gdṿl in Dan 10,1 is disputed, variously translated as “but the time appointed was long,” “extremely hard to understand,” “great conflict” or “great war.” Based on linguistic and contextual evidence, this article provides new additional considerations for the meaning of ṿtsvʾ gdṿl as “great host” or “great war.” The present paper sheds light on the complex nuances of ṿtsvʾ gdṿl and shows its role in revealing the heavenly and earthly warfare described in Dan 10-12.